Comparison of News Literacy, Media Consumption, and Trust Between Indonesia and Malaysia - Facciani, Matthew; Idris, Ika Karlina; Weninger, Tim (Asian Journal of Media and Communication, 2023)
News literacy and trust are essential factors to consider in how individuals navigate their media environments. However, studies on news literacy and trust have focused primarily on Western and English-speaking populations. The current study evaluates and compares news literacy, media consumption, and trust among Indonesian and Malaysian samples. Our data was collected in July 2021 via a telephone survey. We did not find any significant differences in self-reported news literacy between countries, but we found that participants lower in age, college education, and living in an urban area score higher on news literacy across both populations. We also found that our Malaysian participants reported spending more time on social media, but Indonesian participants spent more time watching television. We did not find any significant differences between countries for trust in institutional media, but Indonesian participants reported higher trust in online media. These findings highlight the importance of considering cultural differences in designing and evaluating media literacy interventions.